Food taboos with socioeconomic status during pregnancy in West Kalimantan, Indonesia - Santy Irene Putri; Yefta Yefta; Astri Yunita (Al-Sihah : The Public Health Science Journal, 2020)
Each region in Indonesia has diversity in terms of food consumption patterns, especially for pregnant women, which is accompanied by beliefs about taboos from certain types of food. This study aimed to determine the relationship between age, education level, employment status, and the culture of food taboos in pregnant women. This was an observational analytic study with a cross-sectional approach. The study was conducted in the working area of the Bengkayang Health Center, West Kalimantan, Indonesia. A sample of 30 pregnant women selected by purposive sampling. The dependent variable is the culture of food taboos in pregnancy. The independent variables include age, education, and employment status. The data were collected by a questionnaire and analyzed using multiple linear regression. Education (b = 0.48; 95% CI = 0.10 to 0.85; p = 0.015) and employment status (b = 0.51; 95% CI = 0.19 to 0.84; p = 0.003) had a relationship with the culture of food taboos in pregnancy and were statistically significant. This study also found a relationship between education and employment status with the culture of food taboos in pregnancy.